123k views
2 votes
Tayler tried to evaluate the expression (22-5\times3) + 6(22−5×3)+6left parenthesis, 22, minus, 5, times, 3, right parenthesis, plus, 6. Her work is below. \begin{aligned} &\phantom{=}(22-5\times 3) + 6\\\\ \text{Step }1:\quad&=(22 -15) + 6 \\\\ \text{Step }2:\quad&=7 + 6 \\\\ \text{Step }3:\quad&=1 \end{aligned} Step 1: Step 2: Step 3: ​ =(22−5×3)+6 =(22−15)+6 =7+6 =1 ​

User Everth
by
5.2k points

1 Answer

1 vote

Explanation:

Given the expression that Tayler tried to evaluate as:


(22-5*3) + 6

We will solve this equation using PEDMAS

Multiplication before addition and subtraction

On solving:


Step \ 1\\= (22-5*3) + 6\\= (22-(15)) + 6\\\\Step\ 2\\= (22-15) + 6\\\\Step \ 3\\= 7+6\\= 13

From the steps above, we can see that Tayler made an error in step 3 by taking the difference of 7 and 6 and arriving at 1 instead of summing up to get 13 as shown above.

User Neonidian
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.